Analytical ultracentrifugation and preliminary X‐ray studies of the chloroplast envelope quinone oxidoreductase homologue from Arabidopsis thaliana. Issue 4 (1st April 2015) - Mas y mas, Sarah; Giustini, Cécile; Ferrer, Jean‐Luc; Rolland, Norbert; Curien, Gilles; Cobessi, David
<x xml:space="preserve">Abstract</x> Quinone oxidoreductases reduce a broad range of quinones and are widely distributed among living organisms. The chloroplast envelope quinone oxidoreductase homologue (ceQORH) from Arabidopsis thaliana binds NADPH, lacks a classical N‐terminal and cleavable chloroplast transit peptide, and is transported through the chloroplast envelope membrane by an unknown alternative pathway without cleavage of its internal chloroplast targeting sequence. To unravel the fold of this targeting sequence and its substrate specificity, ceQORH from A. thaliana was overexpressed in Escherichia coli, purified and crystallized. Crystals of apo ceQORH were obtained and a complete data set was collected at 2.34 Å resolution. The crystals belonged to space group C2221, with two molecules in the asymmetric unit.